Dampak Brand Equity Kepada Pelanggan Untuk Melakukan Pembelian Ulang - Bima Jati Pratama; Afrizal Hakam Naja; Dafa Pratama Mulya; Imam Haqqiy Rahmadiyanto; Zevira Linggar Sidhawati (Universitas Muhammadiyah Surakarta, 2026)
The purpose of this study is to examine and understand how various elements of brand equity influence user or consumer behavior in making repeat purchases of a product. Brand equity is considered one of the most valuable strategic assets in marketing activities because of its ability to build customer loyalty and strengthen the brand's position in the minds of consumers. This study adopts a qualitative descriptive approach, with data collection techniques through in-depth interviews with a number of individuals who are active customers of a particular brand. The findings of this study indicate that the dimensions of brand equity, including brand awareness, brand association, perception of quality, and brand loyalty, collectively contribute significantly to consumers' decisions to repurchase. Among these four dimensions, brand loyalty emerges as the most dominant factor in encouraging consumers to continue choosing and purchasing products from the same brand, even in the face of increasingly competitive market conditions. Additionally, the initial impression consumers experience when first interacting with a brand, the emotional bond that develops over time, and the visual appeal of elements such as a distinctive logo and attractive packaging, all contribute to strengthening positive perceptions and fostering loyalty toward the brand. A pleasant initial experience often serves as the starting point for the formation of a long-term relationship between consumers and the brand, which is then reinforced by consistent visual and emotional factors in every interaction to maintain loyalty and enhance customer retention rates in the long term.